The Effect of Earthquakes and Tsunamis Preparedness on Anxiety Levels: A Case Study of Alue Naga Village, Banda Aceh - Ika Mawarni; Taufik Suyadi; Subhan Rio Pamungkas; Vivi Keumala Mutiawati (TDMRC, Universitas Syiah Kuala, 2020)
Preparedness is a new paradigm in the context of disaster management. In order to reduce casualties, property losses, and psychological impacts, the community must improve their preparedness. Alue Naga Village, Banda Aceh is one of the earthquakes and tsunami-prone areas. This study aims at determining the effect of earthquake and tsunami preparedness on the level of community anxiety. It utilized an analytic observational method, with a cross-sectional approach with 100 respondents. Data obtained from questionnaires were analyzed using the Kolmogorov Smirnov test. This study demonstrated that 90% of respondents have low preparedness and 70% have mild anxiety levels. It concluded that there is no significant effect between the earthquake and tsunami preparedness on the level of community anxiety in Alue Naga Village, Banda Aceh, with p value= 0.864 (p 0.1). This study recommends more research, especially on the important aspects of preparedness and anxiety levels.